Novel Concepts in the Management of Angina in Coronary Artery Disease - Theofilis, Panagiotis; Oikonomou, Evangelos; Sagris, Marios; Papageorgiou, Nikolaos; Tsioufis, Konstantinos; Tousoulis, Dimitris (Current Pharmaceutical Design, 2023)
Coronary artery disease remains a condition with high prevalence and detrimental effects on the quality of life of affected individuals. Its most frequent manifestation, stable angina pectoris, may be challenging to manage despite the available antianginal pharmacotherapy and adequate risk factor control, especially in subjects not amenable to revascularization. In the direction of refractory angina pectoris, several approaches have been developed over the years with varying degrees of success. Among the most recognized techniques in managing angina is enhanced external counterpulsation, which utilizes mechanical compression of the lower extremities to increase blood flow to the heart. Moving to coronary sinus reduction, it leads to an increase in coronary sinus backward pressure, ultimately augmenting myocardial blood flow redistribution to ischemic regions and ameliorating chronic angina. Clinical trial results of the above-mentioned techniques have been encouraging but are based on small sample sizes to justify their widespread application. Other interventional approaches, such as transmyocardial laser revascularization, extracorporeal shockwave myocardial revascularization, and spinal cord stimulation, have been met with either controversial or negative results, and their use is not recommended. Lastly, angiogenic therapy with targeted intramyocardial vascular endothelial growth factor injection or CD34+ cell therapy may be beneficial and warrants further investigation. In this review, we summarize the current knowledge in the field of angina management, highlighting the potential and the gaps in the existing evidence that ought to be addressed in future larger-scale, randomized studies before these techniques can be safely adapted in the clinical practice of patients with refractory angina pectoris
Keywords: angiogenic therapy